2019
DOI: 10.1111/jfpp.13884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different drying methods on nutritional composition, physicochemical and functional properties of sweet potato leaves

Abstract: In this study, effects of microwave‐vacuum (MVD), hot‐air (HAD), and vacuum‐freeze (VFD) drying methods on the nutritional composition, physicochemical, and functional properties of sweet potato leaves (SPL) were investigated. VFD–SPL showed higher total dietary fiber, vitamin C, E, B1, and B2, and mineral Mg, P, and Zn content than MVD– and HAD–SPL. MVD–SPL showed highest water absorb index, oil absorption capacity, swelling power and solubility. HAD–SPL had smallest particle size (D[4,3] = 56.85 μm), which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…The moisture content of oven‐ and freeze‐dried rambutan seed powders were found to be 8.33 and 8.46%, respectively, showing no significant difference between the two drying methods. Our results are in line with the results reported by Sui et al, who investigated the effects of different drying methods on nutritional, functional, and physicochemical properties of sweet potato leaves. Jinap et al studied the effects of moisture contents (1.95%‐17.64%) on cocoa butter extraction from ground cocoa nibs.…”
Section: Resultssupporting
confidence: 93%
“…The moisture content of oven‐ and freeze‐dried rambutan seed powders were found to be 8.33 and 8.46%, respectively, showing no significant difference between the two drying methods. Our results are in line with the results reported by Sui et al, who investigated the effects of different drying methods on nutritional, functional, and physicochemical properties of sweet potato leaves. Jinap et al studied the effects of moisture contents (1.95%‐17.64%) on cocoa butter extraction from ground cocoa nibs.…”
Section: Resultssupporting
confidence: 93%
“…There was no significant difference ( p > 0.05) between calcium concentrations determined in Suc-T and Syr-T. Calcium functions as a constituent of bone and teeth, and regulation of nerve and muscle. Calcium is also associated with vitamin D metabolism; and calcium-containing substances are required by children, pregnant and lactating women for bones and teeth development (Olusanya et al , 2019; Sui et al , 2019). The value obtained in this study was high enough to activate the conversion of prothrombin to thrombin (in blood coagulation) and also takes part in milk clotting (Soetan et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…These results imply that drying at low temperatures (<30 °C) may be a suitable method to maintain the nutritional value and bioactive compounds in SPL [ 15 ]. In addition, Sui et al [ 75 ] investigated the influences of vacuum-freeze, hot-air, and microwave-vacuum drying methods on the nutritional composition of SPL, and indicated that the vacuum-freeze drying method maintained the highest vitamins (B1, B2, C, and E), minerals (Zn, P, and Mg), total dietary fiber, and TPC.…”
Section: Bioactive Compounds In Sweet Potato Leavesmentioning
confidence: 99%